Relationship Between Cognition and Gait at 2- and 12-Months Post-Traumatic Brain Injury - Vuong, Veronica; Patterson, Kara K.; Cole, Lauren Patricia; Henechowicz, Tara Lynn; Sheridan, Conor; Green, Robin E. A.; Thaut, Michael H. (Frontiers in Rehabilitation Sciences, 2021)
Background: A common and debilitating challenge experienced by people with TBI is gait-associated mobility impairment and persisting cognitive impairments. Cognitive and physical impairments are often addressed independently during rehabilitation, however, increasing evidence links cognitive and motor processes more closely. Objectives: 1) To determine if correlations exist between measures of cognitive and gait recovery, post-TBI. 2) To investigate the predictive power of cognition at 2-months on gait outcomes at 12-months post-TBI. Methods: In this secondary, longitudinal study of cognitive and neural recovery, data from 93 participants admitted to an inpatient neurorehabilitation program were analyzed. Spatiotemporal gait variables [velocity, step time variability (STV), step length variability (SLV)] were collected along with cognitive variables [Trail Making Test-B (TMT-B), Digit Span-Forward (DS-F)]. Spearman’s correlation coefficients were calculated between gait and cognitive variables. Multilinear and step wise regression analyses were calculated to determine predictive value of cognitive variables at 2-months on gait performance at 12-months-post TBI. Results: At 2-months post-injury, TMT-B was significantly correlated with gait velocity and STV; and DS-F was significantly correlated with velocity. At 12-months post-injury, TMT-B and DS-F was still significant correlated with velocity. TMT-B at 2-months was correlated with SLV and STV at 12-months; and DS-F correlated significantly with velocity. Regression models showed TMT-B at 2-months predicting STV, SLV and velocity at 12-months. Conclusions: Significant associations and predictions between physical and cognitive recovery post-TBI were observed in this study. Future directions may consider a ‘neural internetwork’ model as a salient rehabilitation approach in TBI that integrates physical and cognitive functions.